'A Neo-colonial Education': Querying its Role in Immigrant Identity, Inclusion and Empowerment. (4th March 2021) - Lahiri-Roy, Reshmi; Belford, Nish
ABSTRACT: This article problematises the neo-colonial legacies of Westernised education in the experiences of empowerment, disempowerment and identity negotiations of two immigrant academic women often positioned as 'elite' transnationals in Australia. Through positioning theory and postcolonial theory as frameworks, critical autoethnography as a research method shapes our personal accounts within two postcolonial contexts (India and Mauritius). We explore the tensions and dualities of race, class, ethnicity and gender engendered through an anglicised education. Our empowerment manifests as privilege and access to knowledge and opportunities for transnational mobility. We unpack the gradual erosion of our cultural rootedness and a renegotiation of our migrant identities entailing both submissiveness and resistance. Situating education as a force in our lives, we query whether it is an 'empowerment tool' concomitantly creating and deleting elements of our cultural history OR reclaiming the paradoxes of privilege and 'disempowerment' shaped by a neo-colonial education?